Production and adoption constraints of coffee improved varieties in Jimma zone; Southwest Ethiopia - Chelkeba, Samuel Diro; Erko, Beza; Fikirie, Kalkidan (Journal of Scientific Agriculture, 2019)
The study was aimed to identify major coffee production problems that affected coffee farmers’ production and productivity. The study was conducted in four districts of Jimma zone namely Gera, Manna, Limu Kosa and Gomma. Multistage sampling technique was employed to select the population for the study which involved both purposive and random sampling techniques. Data was collected through structured questionnaire administered to sampled farmers from 285 coffee producing households. Both descriptive and inferential statistics were used to analyze the gathered and cleaned data. Kendall’s coefficient of concordance was used to rank the most important coffee production constraints. The study has identified three top constraints on coffee production. Low and fluctuating coffee price, coffee market information problem and lack of coffee seed and seedling varieties preferred were the major problems explored. Strengthening cooperatives and unions, sustainable supply of improved coffee seeds and seedlings, and sustainable coffee seed system are suggested to tackle coffee production problems.